2016
DOI: 10.1016/j.foodchem.2016.05.042
|View full text |Cite
|
Sign up to set email alerts
|

Multiresponse optimization of an extraction procedure of carnosol and rosmarinic and carnosic acids from rosemary

Abstract: A green solvent-based optimization for rosmarinic acid (RA), carnosol (COH), and carnosic acid (CA) extraction, the three main antioxidants from rosemary, was performed. The conventional solid-liquid extraction was optimized using a central composite design (CCD) followed by the desirability approach. In the CCD analysis the quantitative effects of extraction time (4.8-55.2min), liquid-to-solid ratio (4.6-21.4mLg(-1)), and ethanol content (44.8-95.2% v/v) were determined for the extracted amount of antioxidant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 32 publications
5
49
0
1
Order By: Relevance
“…Moreover, the multi-response optimization to determine the extraction conditions which maximize both yields (TPC and TA yields) was evaluated. This optimization was based on a desirability function (D) obtained through the following equation (Equation 2) [11,31,34,35].…”
Section: Response Surface Methodology (Rsm)mentioning
confidence: 99%
“…Moreover, the multi-response optimization to determine the extraction conditions which maximize both yields (TPC and TA yields) was evaluated. This optimization was based on a desirability function (D) obtained through the following equation (Equation 2) [11,31,34,35].…”
Section: Response Surface Methodology (Rsm)mentioning
confidence: 99%
“…Research efforts focus not only on high-yield extracts rich in bioactive ingredients but also on meeting current energy requirements, such as shorter extraction times, green solvents, and smaller amounts of organic solvents. De AR Oliveira et al [ 8 ] examined mixtures of acetone, methanol, or ethanol with water for the quantitative recovery of rosmarinic acid, carnosol, and carnosic acid and optimized the extraction conditions for the simultaneous extraction of the three compounds with ethanol-water mixtures, through a central composite design. They concluded that, although the optimum yield of each compound varied according to polarity, 70% ethanol in water or 80% acetone in water provided the best additive yield for rosmarinic acid, carnosic acid, and carnosol.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from Oliveira et al. , who optimized the ethanol content to extract RA, CA and carnosol from rosemary , very few studies were carried out to rationalize the ethanol:water mixture. Furthermore, the resulting extracts are generally characterized by their content in active compounds using HPLC, for reasons of simplicity and speed of analysis.…”
Section: Introductionmentioning
confidence: 99%